2013
DOI: 10.1021/ml400267q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Cytotoxicity of Semisynthetic Withalongolide A Analogues

Abstract: The natural product withaferin A exhibits potent antitumor activity and other diverse pharmacological activities. The recently discovered withalongolide A, a C-19 hydroxylated congener of withaferin A, was recently reported to possess cytotoxic activity against head and neck squamous cell carcinomas. Semisynthetic acetylated analogues of withalongolide A were shown to be considerably more cytotoxic than the parent compound. To further explore the structure-activity relationships, 20 new semisynthetic analogues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…In order to better probe the withanolide antiproliferative structural activity relationship model, a total of 27 semi-synthetic withanolide derivatives ( 69 – 95 ) were prepared from natural isolates ( 1 , 19 , 20 , and 33 ) (Figure 5) (Zhang et al 2011; Zhang et al 2012b; Motiwala et al 2013). …”
Section: Withanolide Artifacts and Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to better probe the withanolide antiproliferative structural activity relationship model, a total of 27 semi-synthetic withanolide derivatives ( 69 – 95 ) were prepared from natural isolates ( 1 , 19 , 20 , and 33 ) (Figure 5) (Zhang et al 2011; Zhang et al 2012b; Motiwala et al 2013). …”
Section: Withanolide Artifacts and Derivativesmentioning
confidence: 99%
“…Greater potency was observed in the acetylated derivatives withalongolide A 4,19,27-triacetate ( 79 ), withalongolide B 4,19-diacetate ( 73 ), and withalongolide O 4,7-diacetate ( 71 ), which collectively produced IC 50 values in the 0.067 n M – 2.0 μM range (Zhang et al 2011; Zhang et al 2012b; Motiwala et al 2013). …”
Section: Antiproliferative Evaluation Of Withanolide Librarymentioning
confidence: 99%
“…Cronquist [4], Physalis longifolia Nutt. [5][6][7], and Withania somnifera Dunal [8,9]. Such extensive research afforded a withanolide library that was utilized as part of an extensive structural activity relationship study.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent semi-synthetic experiments were conducted on the most anti-proliferative constituents of the species, such as compound 2, which generated a highly potent withanolide derivative (24) (Fig. 1) [7]. Additional cell proliferation assay testing revealed that withanolides 1, 2, and 24 produced nanomolar IC 50 values (1: 290, 4000, 2000, 800, 200 nM; 2: >10,000, 5100, 5300, 3300 nM, >10,000 nM; and 24: 98 nM; 810 nM; 140 nM; 2200 nM; 410 nM) against melanoma (B16F10 and SKMEL-28), human oral cavity carcinoma (JMAR, and MDA-1986) and normal fetal fibroblast (MRC-5) cells, respectively [5].…”
Section: Introductionmentioning
confidence: 99%
“…Aubé and coworkers reported a series of semisynthetic analogs of withalongolide-A, which is a C-19 hydroxylated analog of withaferin-A (Motiwala et al, 2013). These semisynthetic derivatives are found to be more cytotoxic than the parent molecule against a variety of cell lines (Fig.…”
Section: Chemistrymentioning
confidence: 99%